PENGEMBANGAN BAHAN AJAR CERITA BERGAMBAR BERBASIS LINGKUNGAN PADA MATERI DISEKITAR RUMAH KELAS I SEKOLAH DASAR - Sri Inggit Rachayu; Ujang Jamaludin; Zeri Rahman Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This Research and Development (R&D) is motivated by a needs analysis through observation and interviews at Banjarsari 2 Public Elementary School, which shows the need for contextual teaching materials for the material